2011
DOI: 10.1371/journal.pone.0028825
|View full text |Cite
|
Sign up to set email alerts
|

A Novel N-Acetylglutamate Synthase Architecture Revealed by the Crystal Structure of the Bifunctional Enzyme from Maricaulis maris

Abstract: Novel bifunctional N-acetylglutamate synthase/kinases (NAGS/K) that catalyze the first two steps of arginine biosynthesis and are homologous to vertebrate N-acetylglutamate synthase (NAGS), an essential cofactor-producing enzyme in the urea cycle, were identified in Maricaulis maris and several other bacteria. Arginine is an allosteric inhibitor of NAGS but not NAGK activity. The crystal structure of M. maris NAGS/K (mmNAGS/K) at 2.7 Å resolution indicates that it is a tetramer, in contrast to the hexameric st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 61 publications
(124 reference statements)
2
32
0
Order By: Relevance
“…1). Because both MmNAGS-K and XcNAGS-K are completely inhibited by L-arginine1215 synthase activity of both enzymes was zero after incubation at temperatures between 20 °C and 70 °C in the presence of 1 mM L-arginine (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Because both MmNAGS-K and XcNAGS-K are completely inhibited by L-arginine1215 synthase activity of both enzymes was zero after incubation at temperatures between 20 °C and 70 °C in the presence of 1 mM L-arginine (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies of NAGS from bacteria, fish and mammals revealed that the oligomeric state of some of these proteins changes upon binding of L-arginine112532, while others do not13151624. Because the three-dimensional structure of NgNAGS, whose oligomerization state does not change upon binding of L-arginine, is known1316, while the structure of NAGS from E. coli , whose oligomerization state does change in the presence of L-arginine25 remains elusive, we tested if a similar correlation holds for vertebrate-like MmNAGS-K and XcNAGS-K, both with known three-dimensional structures, though the resolution of XcNAGS-M crystals is lower than the MmNAGS-K crystals15.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations